Low-stress PC / ABS alloy

By adjusting the composition of PC/ABS alloys, including modified talc powder, modified glass micro beads, and enhanced fiber, the problem of high -tough PCABS alloy materials in the injection molding process has significantly improved the toughness and resistance of the material and anti -resistance Stress ability.

CN119331405APending Publication Date: 2025-01-21NANJING JINSHAN AUTOMOBILE ENG PLASTIC

Patent Information

Application Number
CN202411756511.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing high-toughness PCABS alloy materials are prone to internal stress residues during injection molding, which leads to the material being easily broken and prone to white printing problems.

Method used

Using low-stress PC/ABS alloys, through adjustment of ingredients, including 45-65 copies of PC resin, 15-30 copies of ABS resin, 3-6 copies of modified talc powder, 2-5 copies of modified glass micro beads, 5-12 servings of enhanced fiber, 3.5-7.5 subsidizers, and 0.5 copies of internal lubricants can improve the compatibility and decentralization effects of the material, and reduce internal stress residues.

Benefits of technology

Improve the toughness of the material and the impact of tensile resistance, reduce the risk of cracking of the material, and significantly improve the antiplication ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331405A_ABST
    Figure CN119331405A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of plastics, particularly relates to a low-stress PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) alloy, and provides the following scheme aiming at the problems that the existing injection molding internal stress is remained, and breakage and white marks are easily caused. The low-stress PC / ABS alloy is prepared from the following components in parts by mass: 45 to 65 parts of PC resin, 15 to 30 parts of ABS resin, 3 to 6 parts of modified talcum powder, 2 to 5 parts of modified glass beads, 5 to 12 parts of reinforced fibers, 3.5 to 7.5 parts of auxiliaries and 0.5 part of an internal lubricant, wherein the auxiliaries comprise a compatilizer, a toughening agent, a chain extender and an antioxidant; by taking the materials such as the PC resin, the ABS resin, the modified talcum powder, the modified glass beads, the reinforced fibers, the auxiliaries and the internal lubricant, the movement speed of molecules is increased, when the plastic is subjected to external force, the materials are not prone to deformation, stress is not prone to being transmitted or consumed, the toughness of the materials is improved, the tensile and impact resistance of the materials is guaranteed, and cracking is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, and in particular to a low-stress PC / ABS alloy. Background Art

[0002] The Chinese patent document with application number 202311177372.7 discloses a high-toughness PCABS alloy material and a preparation method thereof, wherein the high-toughness PCABS alloy material comprises the following components by mass: 30-60 parts of PC resin, 15-30 parts of ABS resin, 5-10 parts of modified silica, 7-15 parts of glass fiber, 2-5 parts of compatibilizer, and 3-5 parts of auxiliary agent; wherein the modified silica is the product obtained by the reaction of hydroxylated silica and alkyl dibasic acid; the compatibilizer comprises a blend of SMA resin, acrylic resin, and POE resin. The present invention modifies silica, and at the same time uses a blend of SMA resin, acrylic resin, and POE resin as a compatibilizer to compound with materials such as glass fiber, thereby enhancing the compatibility between multiple components and improving the dispersion effect, thereby ensuring the stability of the PCABS alloy material, and at the same time having good mechanical properties such as toughness, thereby overcoming the defects existing in existing products.

[0003] However, there are also some problems with the high-toughness PCABS alloy material and its preparation method. For example, when the material is injected, the molecular chain is elongated under the action of high temperature, and the molecular chain shrinks after cooling. The molecular movement speed is slow. When the plastic is subjected to external force, the object is easy to deform. Due to the slow molecular movement, the external force is not easy to be transmitted (equal distribution of internal stress) or consumed (molecular chain friction), so it is easy to produce internal stress concentration. When the internal stress reaches a certain level, the macromolecules are prone to break and cracks. The cracks will propagate due to the concentration of internal stress, causing the plastic to break. Summary of the invention

[0004] Based on the background technology that there is residual internal stress in injection molding, which easily leads to fracture and white printing, the present invention proposes a low-stress PC / ABS alloy.

[0005] The present invention provides a low stress PC / ABS alloy, which comprises the following components by mass: 45 to 65 parts of PC resin, 15 to 30 parts of ABS resin, 3 to 6 parts of modified talc, 2 to 5 parts of modified glass microspheres, 5 to 12 parts of reinforcing fibers, 3.5 to 7.5 parts of additives and 0.5 parts of internal lubricant: Additives include compatibilizers, toughening agents, chain extenders and antioxidants. By taking materials such as PC resin, ABS resin, modified talcum powder, modified glass beads, reinforcing fibers, additives and internal lubricants, the movement speed of molecules is accelerated. When the plastic is subjected to external force, the material is not easily deformed, and the stress is not easily transmitted or consumed, thereby improving the toughness of the material, ensuring the tensile and impact resistance of the material, and preventing cracking.

[0006] Preferably, the raw materials for preparing the modified talc powder include talc powder raw material, deionized water, dilute hydrochloric acid, 24% ethanol aqueous solution, dioctadecyl dihydroxy ammonium chloride and silane coupling agent, and the volume ratio of talc powder raw material, deionized water, dilute hydrochloric acid and 24% ethanol aqueous solution is controlled at 1:10:1:5, which is convenient for modifying the talc powder.

[0007] Preferably, the preparation method of the modified talc powder is as follows: the talc raw material is roughly selected, and then poured into a grinding equipment for crushing until the talc powder passes a 200-mesh sieve, 10 times the amount of deionized water and 1 times the amount of dilute hydrochloric acid of the talc powder are added, and a high-speed stirring device is used to mix to form a talc slurry, and a 24% ethanol aqueous solution 5 times the volume of the talc powder is poured into it, and stirring is continued. After stirring evenly, pour it into a container and stand for stratification, remove the supernatant, and repeat twice. After purification, purified talc powder is obtained, 7% of the volume of the purified talc powder is added with dioctadecyl dihydroxyammonium chloride and 2% of a silane coupling agent, and mixed for activation. After the activation reaction is completed, the material is filtered, dried, crushed and sieved to obtain modified talc powder, which can enhance the compatibility of the modified talc powder with other materials.

[0008] Preferably, the raw materials for preparing the modified glass microspheres include: glass microspheres and activation gas. The activation gas is a mixture of a silanization modifier and an ethylene glycol aqueous solution, which is gasified to generate activation gas, which can increase the activity of the surface of the modified glass microspheres.

[0009] Preferably, the method for preparing the modified glass microspheres is as follows: the hollow glass microspheres are poured into the cavity of a plasma treatment instrument, the pressure inside the plasma treatment instrument is adjusted to 8 Pa, and then hot air is introduced to clean the glass microspheres, the temperature of the hot air is controlled at 110° C. to 125° C., and the wind speed of the hot air is controlled at 10 m / s to 13 m / s, and then activated gas is introduced to obtain glass microsphere powder from the outlet of the plasma treatment instrument, and then the modified glass microspheres are obtained through curing, thereby enhancing the compatibility of the glass microspheres with other materials and avoiding problems such as material separation.

[0010] Preferably, the reinforcing fiber comprises glass fiber, basalt fiber and a modifier, the ratio of glass fiber to basalt fiber is controlled at 2:1, the modifier is composed of cyanosilane coupling agent, starch, saturated fatty acid glyceride, white oil, dehydrated sorbitan monooleate, bisphenol A type epoxy resin, acetic acid, ammonium chloride, defoaming agent and the balance of deionized water, and the reinforcing fiber can enhance the strength and toughness of the material.

[0011] Preferably, the reinforcing fiber modification method comprises obtaining glass fiber and basalt fiber, soaking the glass fiber and basalt fiber in a modifier, and after soaking for 2 hours, obtaining modified glass fiber, which can improve the compatibility of the reinforcing fiber with other materials.

[0012] Preferably, the weight ratio of the compatibilizer, toughening agent, chain extender and antioxidant is controlled at 4:3:1:2, the compatibilizer is composed of SAN, LLDPE-g-MAH, MBS and SMA, and the chain extender is an oxaline type chain extender with the brand BASF ADR4370S to ensure the performance of the material.

[0013] Preferably, the toughening agent is ABS high-rubber powder, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is controlled at 1:1 to ensure the toughness and oxidation resistance of the material.

[0014] Preferably, the preparation method of the PC / ABS alloy is as follows: PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant are weighed in proportion, added into the interior of a high-speed mixing device, mixed for 5 minutes to 15 minutes to obtain a mixture, the mixture is put into an extruder, heated to melt, extruded and granulated to obtain a low-stress PC / ABS alloy.

[0015] Beneficial effects of the present invention: By taking materials such as PC resin, ABS resin, modified talcum powder, modified glass beads, reinforcing fiber, additives and internal lubricants, the movement speed of molecules is accelerated. When the plastic is subjected to external force, the material is not easy to deform, the stress is not easy to be transmitted or consumed, and the toughness of the material is improved, ensuring the tensile and impact resistance of the material and preventing cracking. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The working flow chart proposed by the present invention. DETAILED DESCRIPTION

[0017] The present invention will be further explained below in conjunction with specific embodiments.

[0018] Reference Figure 1 , Embodiment 1 In this embodiment, a low stress PC / ABS alloy is proposed. The low stress PC / ABS alloy includes the following components by mass: 50 parts of PC resin, 20 parts of ABS resin, 5 parts of modified talc powder, 5 parts of modified glass microspheres, 12 parts of reinforcing fiber, 7.5 parts of additives and 0.5 parts of internal lubricant: Additives include compatibilizers, toughening agents, chain extenders and antioxidants; The raw materials for preparing the modified talc powder include talc powder raw material, deionized water, dilute hydrochloric acid, 24% ethanol aqueous solution, dioctadecyl dihydroxy ammonium chloride and silane coupling agent, and the volume ratio of the talc powder raw material, deionized water, dilute hydrochloric acid and 24% ethanol aqueous solution is controlled at 1:10:1:5; Preparation method of modified talcum powder: roughly selecting talcum powder raw materials, then pouring into grinding equipment for crushing until the talcum powder passes through a 200-mesh sieve, adding 10 times the amount of deionized water and 1 times the amount of dilute hydrochloric acid as the talcum powder, using a high-speed stirring device to mix to form a talcum powder slurry, pouring 5 times the volume of 24% ethanol aqueous solution of the talcum powder, continuing to stir, stirring evenly, pouring into a container and standing for stratification, removing the supernatant, repeating twice, after purification, obtaining purified talcum powder, adding 7% of the volume of the purified talcum powder dioctadecyl dihydroxyammonium chloride and 2% of a silane coupling agent, mixing and activating, after the activation reaction is completed, filtering, drying, crushing and sieving the material to obtain modified talcum powder; The raw materials for preparing the modified glass microspheres include: glass microspheres and activation gas, wherein the activation gas is a mixture of a silanization modifier and an ethylene glycol aqueous solution, which is gasified to generate the activation gas; The method for preparing modified glass microspheres is as follows: hollow glass microspheres are poured into a plasma treatment chamber, the pressure inside the plasma treatment chamber is adjusted to 8 Pa, and then hot air is introduced to clean the glass microspheres, the temperature of the hot air is controlled at 110° C. to 125° C., and the wind speed of the hot air is controlled at 10 m / s to 13 m / s, and then activated gas is introduced to obtain glass microsphere powder from the outlet of the plasma treatment chamber, and then the modified glass microspheres are obtained through curing. The reinforcing fiber includes glass fiber, basalt fiber and a modifier, the ratio of glass fiber to basalt fiber is controlled at 2:1, and the modifier is composed of cyanosilane coupling agent, starch, saturated fatty acid glyceride, white oil, dehydrated sorbitan monooleate, bisphenol A type epoxy resin, acetic acid, ammonium chloride, defoaming agent and the balance of deionized water; Modification method of reinforcing fiber: obtain glass fiber and basalt fiber, put the glass fiber and basalt fiber into a modifier for soaking, and after soaking for 2 hours, the modified glass fiber is obtained; The weight ratio of compatibilizer, toughening agent, chain extender and antioxidant is controlled at 4:3:1:2. The compatibilizer is composed of SAN, LLDPE-g-MAH, MBS and SMA. The chain extender is an oxaline chain extender with a brand of BASF ADR4370S. The toughening agent is ABS high-rubber powder, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is controlled at 1:1; Preparation method of PC / ABS alloy: PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant are weighed in proportion, added into the interior of a high-speed mixing device, mixed for 5 to 15 minutes to obtain a mixture, and the mixture is put into an extruder, heated to melt, extruded and granulated to obtain a low-stress PC / ABS alloy.

[0019] Reference Figure 1 , Embodiment 2 In this embodiment, a low stress PC / ABS alloy is proposed. The low stress PC / ABS alloy includes the following components by mass: 50 parts of PC resin, 25 parts of ABS resin, 6 parts of modified talc powder, 4 parts of modified glass microspheres, 8 parts of reinforcing fiber, 6.5 parts of additives and 0.5 parts of internal lubricant: Additives include compatibilizers, toughening agents, chain extenders and antioxidants; The raw materials for preparing the modified talc powder include talc powder raw material, deionized water, dilute hydrochloric acid, 24% ethanol aqueous solution, dioctadecyl dihydroxy ammonium chloride and silane coupling agent, and the volume ratio of the talc powder raw material, deionized water, dilute hydrochloric acid and 24% ethanol aqueous solution is controlled at 1:10:1:5; Preparation method of modified talcum powder: roughly selecting talcum powder raw materials, then pouring into grinding equipment for crushing until the talcum powder passes through a 200-mesh sieve, adding 10 times the amount of deionized water and 1 times the amount of dilute hydrochloric acid as the talcum powder, using a high-speed stirring device to mix to form a talcum powder slurry, pouring 5 times the volume of 24% ethanol aqueous solution of the talcum powder, continuing to stir, stirring evenly, pouring into a container and standing for stratification, removing the supernatant, repeating twice, after purification, obtaining purified talcum powder, adding 7% of the volume of the purified talcum powder dioctadecyl dihydroxyammonium chloride and 2% of a silane coupling agent, mixing and activating, after the activation reaction is completed, filtering, drying, crushing and sieving the material to obtain modified talcum powder; The raw materials for preparing the modified glass microspheres include: glass microspheres and activation gas, wherein the activation gas is a mixture of a silanization modifier and an ethylene glycol aqueous solution, which is gasified to generate the activation gas; The method for preparing modified glass microspheres is as follows: hollow glass microspheres are poured into a plasma treatment chamber, the pressure inside the plasma treatment chamber is adjusted to 8 Pa, and then hot air is introduced to clean the glass microspheres, the temperature of the hot air is controlled at 110° C. to 125° C., and the wind speed of the hot air is controlled at 10 m / s to 13 m / s, and then activated gas is introduced to obtain glass microsphere powder from the outlet of the plasma treatment chamber, and then the modified glass microspheres are obtained through curing. The reinforcing fiber includes glass fiber, basalt fiber and a modifier, the ratio of glass fiber to basalt fiber is controlled at 2:1, and the modifier is composed of cyanosilane coupling agent, starch, saturated fatty acid glyceride, white oil, dehydrated sorbitan monooleate, bisphenol A type epoxy resin, acetic acid, ammonium chloride, defoaming agent and the balance of deionized water; Modification method of reinforcing fiber: obtain glass fiber and basalt fiber, put the glass fiber and basalt fiber into a modifier for soaking, and after soaking for 2 hours, the modified glass fiber is obtained; The weight ratio of compatibilizer, toughening agent, chain extender and antioxidant is controlled at 4:3:1:2. The compatibilizer is composed of SAN, LLDPE-g-MAH, MBS and SMA. The chain extender is an oxaline chain extender with a brand of BASF ADR4370S. The toughening agent is ABS high-rubber powder, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is controlled at 1:1; Preparation method of PC / ABS alloy: PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant are weighed in proportion, added into the interior of a high-speed mixing device, mixed for 5 to 15 minutes to obtain a mixture, and the mixture is put into an extruder, heated to melt, extruded and granulated to obtain a low-stress PC / ABS alloy.

[0020] Reference Figure 1 , Embodiment 3 In this embodiment, a low stress PC / ABS alloy is proposed. The low stress PC / ABS alloy includes the following components by mass: 55 parts of PC resin, 23 parts of ABS resin, 5 parts of modified talc powder, 3 parts of modified glass microspheres, 8 parts of reinforcing fiber, 5.5 parts of additives and 0.5 parts of internal lubricant: Additives include compatibilizers, toughening agents, chain extenders and antioxidants; The raw materials for preparing the modified talc powder include talc powder raw material, deionized water, dilute hydrochloric acid, 24% ethanol aqueous solution, dioctadecyl dihydroxy ammonium chloride and silane coupling agent, and the volume ratio of the talc powder raw material, deionized water, dilute hydrochloric acid and 24% ethanol aqueous solution is controlled at 1:10:1:5; Preparation method of modified talcum powder: roughly selecting talcum powder raw materials, then pouring into grinding equipment for crushing until the talcum powder passes through a 200-mesh sieve, adding 10 times the amount of deionized water and 1 times the amount of dilute hydrochloric acid as the talcum powder, using a high-speed stirring device to mix to form a talcum powder slurry, pouring 5 times the volume of 24% ethanol aqueous solution of the talcum powder, continuing to stir, stirring evenly, pouring into a container and standing for stratification, removing the supernatant, repeating twice, after purification, obtaining purified talcum powder, adding 7% of the volume of the purified talcum powder dioctadecyl dihydroxyammonium chloride and 2% of a silane coupling agent, mixing and activating, after the activation reaction is completed, filtering, drying, crushing and sieving the material to obtain modified talcum powder; The raw materials for preparing the modified glass microspheres include: glass microspheres and activation gas, wherein the activation gas is a mixture of a silanization modifier and an ethylene glycol aqueous solution, which is gasified to generate the activation gas; The method for preparing modified glass microspheres is as follows: hollow glass microspheres are poured into a plasma treatment chamber, the pressure inside the plasma treatment chamber is adjusted to 8 Pa, and then hot air is introduced to clean the glass microspheres, the temperature of the hot air is controlled at 110° C. to 125° C., and the wind speed of the hot air is controlled at 10 m / s to 13 m / s, and then activated gas is introduced to obtain glass microsphere powder from the outlet of the plasma treatment chamber, and then the modified glass microspheres are obtained through curing. The reinforcing fiber includes glass fiber, basalt fiber and a modifier, the ratio of glass fiber to basalt fiber is controlled at 2:1, and the modifier is composed of cyanosilane coupling agent, starch, saturated fatty acid glyceride, white oil, dehydrated sorbitan monooleate, bisphenol A type epoxy resin, acetic acid, ammonium chloride, defoaming agent and the balance of deionized water; Modification method of reinforcing fiber: obtain glass fiber and basalt fiber, put the glass fiber and basalt fiber into a modifier for soaking, and after soaking for 2 hours, the modified glass fiber is obtained; The weight ratio of compatibilizer, toughening agent, chain extender and antioxidant is controlled at 4:3:1:2. The compatibilizer is composed of SAN, LLDPE-g-MAH, MBS and SMA. The chain extender is an oxaline chain extender with a brand of BASF ADR4370S. The toughening agent is ABS high-rubber powder, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is controlled at 1:1; Preparation method of PC / ABS alloy: PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant are weighed in proportion, added into the interior of a high-speed mixing device, mixed for 5 to 15 minutes to obtain a mixture, and the mixture is put into an extruder, heated to melt, extruded and granulated to obtain a low-stress PC / ABS alloy.

[0021] Reference Figure 1 , Embodiment 4 In this embodiment, a low stress PC / ABS alloy is proposed. The low stress PC / ABS alloy includes the following components by mass: 60 parts of PC resin, 21 parts of ABS resin, 4 parts of modified talc powder, 3 parts of modified glass microspheres, 7 parts of reinforcing fiber, 4.5 parts of additives and 0.5 parts of internal lubricant: Additives include compatibilizers, toughening agents, chain extenders and antioxidants; The raw materials for preparing the modified talc powder include talc powder raw material, deionized water, dilute hydrochloric acid, 24% ethanol aqueous solution, dioctadecyl dihydroxy ammonium chloride and silane coupling agent, and the volume ratio of the talc powder raw material, deionized water, dilute hydrochloric acid and 24% ethanol aqueous solution is controlled at 1:10:1:5; Preparation method of modified talcum powder: roughly selecting talcum powder raw materials, then pouring into grinding equipment for crushing until the talcum powder passes through a 200-mesh sieve, adding 10 times the amount of deionized water and 1 times the amount of dilute hydrochloric acid as the talcum powder, using a high-speed stirring device to mix to form a talcum powder slurry, pouring 5 times the volume of 24% ethanol aqueous solution of the talcum powder, continuing to stir, stirring evenly, pouring into a container and standing for stratification, removing the supernatant, repeating twice, after purification, obtaining purified talcum powder, adding 7% of the volume of the purified talcum powder dioctadecyl dihydroxyammonium chloride and 2% of a silane coupling agent, mixing and activating, after the activation reaction is completed, filtering, drying, crushing and sieving the material to obtain modified talcum powder; The raw materials for preparing the modified glass microspheres include: glass microspheres and activation gas, wherein the activation gas is a mixture of a silanization modifier and an ethylene glycol aqueous solution, which is gasified to generate the activation gas; The method for preparing modified glass microspheres is as follows: hollow glass microspheres are poured into a plasma treatment chamber, the pressure inside the plasma treatment chamber is adjusted to 8 Pa, and then hot air is introduced to clean the glass microspheres, the temperature of the hot air is controlled at 110° C. to 125° C., and the wind speed of the hot air is controlled at 10 m / s to 13 m / s, and then activated gas is introduced to obtain glass microsphere powder from the outlet of the plasma treatment chamber, and then the modified glass microspheres are obtained through curing. The reinforcing fiber includes glass fiber, basalt fiber and a modifier, the ratio of glass fiber to basalt fiber is controlled at 2:1, and the modifier is composed of cyanosilane coupling agent, starch, saturated fatty acid glyceride, white oil, dehydrated sorbitan monooleate, bisphenol A type epoxy resin, acetic acid, ammonium chloride, defoaming agent and the balance of deionized water; Modification method of reinforcing fiber: obtain glass fiber and basalt fiber, put the glass fiber and basalt fiber into a modifier for soaking, and after soaking for 2 hours, the modified glass fiber is obtained; The weight ratio of compatibilizer, toughening agent, chain extender and antioxidant is controlled at 4:3:1:2. The compatibilizer is composed of SAN, LLDPE-g-MAH, MBS and SMA. The chain extender is an oxaline chain extender with a brand of BASF ADR4370S. The toughening agent is ABS high-rubber powder, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is controlled at 1:1; Preparation method of PC / ABS alloy: PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant are weighed in proportion, added into the interior of a high-speed mixing device, mixed for 5 to 15 minutes to obtain a mixture, and the mixture is put into an extruder, heated to melt, extruded and granulated to obtain a low-stress PC / ABS alloy.

[0022] Reference Figure 1 Embodiment 5 In this embodiment, a low stress PC / ABS alloy is proposed. The low stress PC / ABS alloy includes the following components by mass: 65 parts of PC resin, 20 parts of ABS resin, 3 parts of modified talc powder, 2 parts of modified glass microspheres, 6 parts of reinforcing fiber, 3.5 parts of additives and 0.5 parts of internal lubricant: Additives include compatibilizers, toughening agents, chain extenders and antioxidants; The raw materials for preparing the modified talc powder include talc powder raw material, deionized water, dilute hydrochloric acid, 24% ethanol aqueous solution, dioctadecyl dihydroxy ammonium chloride and silane coupling agent, and the volume ratio of the talc powder raw material, deionized water, dilute hydrochloric acid and 24% ethanol aqueous solution is controlled at 1:10:1:5; Preparation method of modified talcum powder: roughly selecting talcum powder raw materials, then pouring into grinding equipment for crushing until the talcum powder passes through a 200-mesh sieve, adding 10 times the amount of deionized water and 1 times the amount of dilute hydrochloric acid as the talcum powder, using a high-speed stirring device to mix to form a talcum powder slurry, pouring 5 times the volume of 24% ethanol aqueous solution of the talcum powder, continuing to stir, stirring evenly, pouring into a container and standing for stratification, removing the supernatant, repeating twice, after purification, obtaining purified talcum powder, adding 7% of the volume of the purified talcum powder dioctadecyl dihydroxyammonium chloride and 2% of a silane coupling agent, mixing and activating, after the activation reaction is completed, filtering, drying, crushing and sieving the material to obtain modified talcum powder; The raw materials for preparing the modified glass microspheres include: glass microspheres and activation gas, wherein the activation gas is a mixture of a silanization modifier and an ethylene glycol aqueous solution, which is gasified to generate the activation gas; The method for preparing modified glass microspheres is as follows: hollow glass microspheres are poured into a plasma treatment chamber, the pressure inside the plasma treatment chamber is adjusted to 8 Pa, and then hot air is introduced to clean the glass microspheres, the temperature of the hot air is controlled at 110° C. to 125° C., and the wind speed of the hot air is controlled at 10 m / s to 13 m / s, and then activated gas is introduced to obtain glass microsphere powder from the outlet of the plasma treatment chamber, and then the modified glass microspheres are obtained through curing. The reinforcing fiber includes glass fiber, basalt fiber and a modifier, the ratio of glass fiber to basalt fiber is controlled at 2:1, and the modifier is composed of cyanosilane coupling agent, starch, saturated fatty acid glyceride, white oil, dehydrated sorbitan monooleate, bisphenol A type epoxy resin, acetic acid, ammonium chloride, defoaming agent and the balance of deionized water; Modification method of reinforcing fiber: obtain glass fiber and basalt fiber, put the glass fiber and basalt fiber into a modifier for soaking, and after soaking for 2 hours, the modified glass fiber is obtained; The weight ratio of compatibilizer, toughening agent, chain extender and antioxidant is controlled at 4:3:1:2. The compatibilizer is composed of SAN, LLDPE-g-MAH, MBS and SMA. The chain extender is an oxaline chain extender with a brand of BASF ADR4370S. The toughening agent is ABS high-rubber powder, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is controlled at 1:1; Preparation method of PC / ABS alloy: PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant are weighed in proportion, added into the interior of a high-speed mixing device, mixed for 5 to 15 minutes to obtain a mixture, and the mixture is put into an extruder, heated to melt, extruded and granulated to obtain a low-stress PC / ABS alloy.

[0023] Comparing conventional PC / ABS alloys with the PC / ABS alloys prepared in Examples 1 to 5, the PC / ABS alloys prepared in Examples 1 to 5 are shown in the following table: Comparative Example Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Embodiment 5 Diameter of stress whitening area (mm) 14.6 3.5 3.1 3.5 3.7 4.2 Visual inspection of the bend to see whitening (times) 127 271 272 268 263 257 At room temperature, the PC / ABS alloys of Examples 1-5 and the comparative example prepared above were each prepared into 10 plastic plates of 100 mm×100 mm×3 mm, and a steel ball weighing 500 g and having a diameter of 50 mm was dropped from a height of 300 mm onto the plastic plate for testing, and then the diameter of the whitened area was recorded and its average value was calculated; At room temperature, the PC / ABS alloys of Examples 1-5 and the comparative example prepared above were each prepared into 10 plastic strips of 50 mm×5 mm×0.8 mm, which were repeatedly bent manually, and the number of bending times was measured to calculate the average value.

[0024] It can be seen from the above table that the stress resistance of the PC / ABS alloy prepared in the present invention is significantly improved, and implementation 2 is the best implementation example.

[0025] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A low stress PC / ABS alloy, characterized in that: The low stress PC / ABS alloy comprises the following components in parts by mass: 45 to 65 parts of PC resin, 15 to 30 parts of ABS resin, 3 to 6 parts of modified talc powder, 2 to 5 parts of modified glass microspheres, 5 to 12 parts of reinforcing fibers, 3.5 to 7.5 parts of additives and 0.5 parts of internal lubricant: Additives include compatibilizers, toughening agents, chain extenders and antioxidants.

2. A low stress PC / ABS alloy according to claim 1, characterized in that: The raw materials for preparing the modified talc powder include talc powder raw material, deionized water, dilute hydrochloric acid, 24% ethanol aqueous solution, dioctadecyl dihydroxy ammonium chloride and silane coupling agent, and the volume ratio of talc powder raw material, deionized water, dilute hydrochloric acid and 24% ethanol aqueous solution is controlled at 1:10:1:

5.

3. A low stress PC / ABS alloy according to claim 2, characterized in that: The preparation method of the modified talcum powder comprises the following steps: roughly selecting a talcum powder raw material, pouring it into a grinding device for crushing until the talcum powder passes through a 200-mesh sieve, adding 10 times the amount of deionized water and 1 times the amount of dilute hydrochloric acid of the talcum powder, mixing them with a high-speed stirring device to prepare a talcum powder slurry, pouring a 24% ethanol aqueous solution 5 times the volume of the talcum powder, continuing to stir, and pouring it into a container to stand for stratification after stirring evenly, removing the supernatant, repeating twice, and after purification, obtaining purified talcum powder, adding 7% of the volume of the purified talcum powder with dioctadecyl dihydroxyammonium chloride and 2% of a silane coupling agent, mixing and activating, and after the activation reaction is completed, filtering, drying, crushing and sieving the material to obtain the modified talcum powder.

4. A low stress PC / ABS alloy according to claim 1, characterized in that: The raw materials for preparing the modified glass microspheres include glass microspheres and activation gas. The activation gas is a mixture of a silane modifier and an ethylene glycol aqueous solution, which is gasified to generate the activation gas.

5. A low stress PC / ABS alloy according to claim 4, characterized in that: The method for preparing the modified glass microspheres comprises the following steps: pouring hollow glass microspheres into a plasma treatment chamber, adjusting the pressure inside the plasma treatment chamber to 8 Pa, introducing hot air to clean the glass microspheres, controlling the temperature of the hot air at 110° C. to 125° C., and controlling the wind speed of the hot air at 10 m / s to 13 m / s, then introducing activated gas, obtaining glass microsphere powder from the outlet of the plasma treatment chamber, and then obtaining the modified glass microspheres through curing.

6. A low stress PC / ABS alloy according to claim 1, characterized in that: The reinforcing fiber comprises glass fiber, basalt fiber and a modifier, wherein the ratio of the glass fiber to the basalt fiber is controlled at 2:1, and the modifier comprises a cyanosilane coupling agent, starch, saturated fatty acid glyceride, white oil, dehydrated sorbitan monooleate, bisphenol A epoxy resin, acetic acid, ammonium chloride, a defoaming agent and the remainder of deionized water.

7. A low stress PC / ABS alloy according to claim 6, characterized in that: The reinforcing fiber modification method comprises the following steps: obtaining glass fiber and basalt fiber, and soaking the glass fiber and basalt fiber in a modifier, and after soaking for 2 hours, obtaining the modified glass fiber.

8. The low stress PC / ABS alloy according to claim 1, characterized in that: The weight ratio of the compatibilizer, toughening agent, chain extender and antioxidant is controlled at 4:3:1:

2. The compatibilizer is composed of SAN, LLDPE-g-MAH, MBS and SMA. The chain extender is an oxaline chain extender with a brand of BASF ADR4370S.

9. A low stress PC / ABS alloy according to claim 1, characterized in that: The toughening agent is ABS high-rubber powder, the antioxidants are antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is controlled at 1:

1.

10. The low stress PC / ABS alloy according to claim 1, characterized in that: The preparation method of the PC / ABS alloy comprises the following steps: weighing PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant according to a certain proportion, adding the PC resin, ABS resin, modified talcum powder, modified glass microbeads, reinforcing fiber, additives and internal lubricant into a high-speed mixing device, mixing the mixture for 5 to 15 minutes to obtain a mixture, putting the mixture into an extruder, heating and melting, extruding and granulating the mixture to obtain a low-stress PC / ABS alloy.

Citation Information

Patent Citations

  • A high-toughness PCABS alloy material and its preparation method

    CN116925517B

Cited By

  • Low-stress high-toughness PC-ABS modified plastic alloy material and preparation method thereof

    CN120504947A